Quality education for Latin American countries: analysis and contributions from the Policy on Educational Success of Quebec - Camillo, Everton da Silva [UNESP]; Boccanfuso, Dorothee; Castro Filho, Claudio Marcondes de (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2020)
This paper aimed at presenting recommendations on high-quality education to Latin American countries' governments by taking the Policy on Educational Success of Quebec as Quebec's main official document to achieve quality education. By using the content analysis method, it was investigated the extent to which the Policy on Educational Success of Quebec adheres to the Sustainable Development Goal (SDG) number 4 (Quality Education), as well as it was analyzed the concordance of the most significant words from the same policy. Findings demonstrate that the Policy on Educational Success of Quebec comprises acts that mostly go towards the promotion of equitable development of the people, to people's learning, skills, and competences, and to the quality in teaching and in learning processes, and in learning spaces. In contrast, the acts that are less significant in the analysis but equally fundamental for the development of society are related to the minimum conditions to achieve quality education, and to the vocational training to foster quality education. Moreover, it was comprehended that the ensuring of quality education in Latin American countries can immediately be linked to some scopes, like the student, school, service, and education ones. This paper concludes that Latin American countries governments can support ensuring quality education for their peoples whether they give special attention to the student, school, service, and education scopes in society.
Keywords: Education Policy; 2030 Agenda; Latin America; Canada; Quebec